Effects of grain alignment efficiency on synthetic dust polarization observations of molecular clouds. Issue 2 (21st September 2019) - King, Patrick K; Chen, Che-Yu; Fissel, L M; Li, Zhi-Yun
ABSTRACT: It is well known that the polarized continuum emission from magnetically aligned dust grains is determined to a large extent by local magnetic field structure. However, the observed significant anticorrelation between polarization fraction and column density may be strongly affected, perhaps even dominated by variations in grain alignment efficiency with local conditions, in contrast to standard assumptions of a spatially homogeneous grain alignment efficiency. Here we introduce a generic way to incorporate heterogeneous grain alignment into synthetic polarization observations of molecular clouds (MCs), through a simple model where the grain alignment efficiency depends on the local gas density as a power law. We justify the model using results derived from radiative torque alignment theory. The effects of power-law heterogeneous alignment models on synthetic observations of simulated MCs are presented. We find that the polarization fraction-column density correlation can be brought into agreement with observationally determined values through heterogeneous alignment, though there remains degeneracy with the relative strength of cloud-scale magnetized turbulence and the mean magnetic field orientation relative to the observer. We also find that the dispersion in polarization angles-polarization fraction correlation remains robustly correlated despite the simultaneous changes to both observables in the presence of heterogeneous alignment.